In Vitro, In Silico Elucidation of Antiurease Activity, Kinetic Mechanism and COX‐2 Inhibitory Efficacy of Coagulansin A of Withania coagulans. Issue 1 (8th January 2018) - Phull, Abdul Rehman; Hassan, Mubshir; Abbas, Qamar; Raza, Hussain; Haq, Ihsan ul; Seo, Sung Yum; Kim, Song Ja
Abstract : Urease enzyme plays a crucial role in the survival of Helicobacter pylori that contributes to different diseases, including peptic ulcer (gastric and duodenal ulcers). Coagulansin A is the steroidal lactone (withanolide) found in plants of solanaceae family such Withania coagulans . The current study was carried out to examine the in vitro urease, COX‐2 inhibitory activity and effect on type II collagen expression of coagulansin A. Moreover, we investigated cytotoxic effects on rabbit articular chondrocytes through MTT assay. COX‐2 and type II collagen expressions were determined through a Western blot method. Molecular docking and simulation studies of urease (PDBID 4H9M) and COX‐2 (PDBID 5F1A) proteins were also performed as an in silico approach. Results showed that COX‐2 expression was decreased dose dependably, significantly higher expression of type II collagen was observed at higher doses. In the current study, coagulansin A was found as non‐toxic, and showed notable urease inhibitory activity in non‐competitive manner with IC 50 23.14 μm in comparison to reference drug thiourea 17.81 μm . Significant decrease in COX‐2 expression (40%) and increase in type II collagen (20%) were observed as compared to control. In silico results unveiled the strong binding affinities of coagulansin A with both of these urease and COX‐2 proteins. Therefore, herein we proposed the significant antiurease potential of this compound that could be used in treating different diseases such as ulcers. Moreover, detailed in vivo studies and molecular mechanism based studies are suggested. Abstract :